Efficacy and tolerability of tricyclic antidepressants and SSRIs compared with placebo for treatment of depression in primary care: A meta-analysis - Arroll, Bruce; Macgillivray, Steve; Ogston, Simon; Reid, Ian; Sullivan, Frank; Williams, Brian; Crombie, Iain (Annals of Family Medicine, 2005)
Purpose: Depression is common in primary care. There are no systematic reviews of depression treatment comparing antidepressants with placebo; hence, we do not know whether these medications are effective in primary care. Methods: We searched the Cochrane Collaboration Depression, Anxiety and Neurosis Group register of controlled trials, MEDLINE, International Pharmaceutical abstracts, PsycINFO, and EMBASE. Abstracts of potential studies were reviewed independently by 2 authors. Studies needed to include randomized controlled trials of either a tricyclic antidepressant (TCA) or selective serotonin reuptake inhibitor (SSRI), or both, and placebo in a primary care setting. The data and quality of the studies were extracted and assessed by 2 authors blind to the other's choice. Disagreements were resolved by discussion. The main outcome measures were the standardized mean difference and weighted mean difference of the final mean depression scores, the relative risk of improvement, and the number withdrawing because of side effects. Pooling of results was done using Review Manager 4.2.2. Results: There were 10 studies in which TCAs were compared with placebo, 3 in which SSRIs were compared with placebo, and 2 with both compared with placebo. One half of the studies were of low methodological quality, and nearly all studies were of short duration, typically 6 to 8 weeks. Pooled estimates of efficacy data showed a relative risk of 1.26 (95% CI, 1.12-1.42) for improvement with TCAs compared with placebo; for SSRIs, relative risk was 1.37 (95% CI, 1.21-1.55). Most patients, 56% to 60%, responded well to active treatment compared with 42% to 47% for placebo. The number needed to treat for TCAs was about 4, and for SSRIs it was 6. The numbers needed to harm (for withdrawal caused by side effects) ranged from 5 to 11 for TCAs and 21 to 94 for SSRIs. Low-dose (100 mg or 75 mg) as well as high-dose TCAs were effective. Conclusion: This systematic review is the first comparing antidepressants with placebo for treatment of depression in primary care. Both TCAs and SSRIs are effective. This review is also the first to show that low-dose TCAs are effective in primary care. Prescribing antidepressants in primary care is a more effective clinical activity than prescribing placebo. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Antidepressant Drugs; Antidepressive Agents, Tricyclic; Depressive Disorder; Humans; Major Depression; Mental Health; Placebo Effect; Placebos; Primary Health Care; Randomized Controlled Trials as Topic; SSRIs; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; depression; efficacy; primary care; tolerability; treatment; tricyclic antidepressants